일부 치위생과 학생의 구강건강행위와 구강병 발생요인 간의 관계 - 임순환(Soon-Hwan Lim); 황지민(Ji-Min Hwang) (한국콘텐츠학회 논문지, 18(3), 2018)
The purpose of this study was to investigate the relationship between oral health behaviors and the results of the oral dysentery test for dental hygienists and students at Gyeonggi - do and Chungcheongnam - do. Self - filling questionnaires and oral diseases. The following conclusions were obtained. The most common toothbrushing frequency was three times a day (60.2%), and the most dominant frequency of eating between meals was once or less(49.7%). The most common snack that they had was stickiness-free sweetened food(66.5%), and the type of beverage that they had the most was sweetened beverages(49.7%). The average stimulated saliva flow rate was 9.41ml, and they got a mean of 9.52 in the buffering capacity of saliva. The average glucose clearance time was a mean of 12.02. When they took a streptococcus mutans colony count test, 80.1 percent belonged to the low-risk group(<$10^5$), and 82.6 percent belonged to the low-risk group(<$10^5$) when a lactobacillus test was conducted. There was a positive correlation between the irritant saliva fraction and the non-irritating saliva and saliva buffering ability. In the fluoride application experience, the glucose retention time was 10.66 minutes and the fluoride application experience was 13.33 minutes. (P = .008). The importance of oral health, which is directly linked to general health, should be emphasized in order to improve the quality of life as well as the life expectancy. For oral health, which is directly linked to systemic health, it is necessary to provide opportunities for oral health education that can be easily accessed by the public, and to continuously develop and provide oral health care programs for a lifetime. 본 연구는 구강건강행위와 구강병 발생요인검사결과와의 관련성을 확인하고자 경기도와 충청남도에 소재한 대학의 치위생과 학생을 대상으로 진행되었다. 자기기입식 설문지 작성과 구강병 발생요인검사로 진행되었으며 다음과 같은 결론을 얻었다. 칫솔질 횟수는 1일 3회가 60.2%, 1일 간식 횟수는 1회 이하가 49.7%, 간식의 종류는 점착성이 없는 가당 간식이 66.5%, 음료수의 종류는 유가당 음료수가 49.7%로 가장 높게 나타났다. 자극성 타액 분비율은 평균 9.41ml, 타액 완충능력은 평균 9.52점, 포도당 잔류시간은 평균 12.02분으로 조사되었다. Streptococcus mutans colony count 검사에서 저위험군인 <$10^5$은 80.1%, Lactobacillus는 저위험군인 <$10^5$은 82.6%로 조사되었다. 자극성 타액 분비율과 비자극성 타액 및 타액 완충능은 양의 상관관계를 보였으며, 불소도포 경험이 있는 경우 포도당 잔류시간이 10.66분, 불소도포 경험이 없는 경우 13.33분으로 나타나 통계적으로 유의한 차이를 보였다(p=.008). 전신건강과 직결되어 있는 구강건강을 위해서는 대중들이 쉽게 접할 수 있는 구강보건교육의 기회를 마련하고, 평생구강건강관리 프로그램을 지속적으로 개발 및 제공해야 할 것으로 사료된다.